PERAN PENGAWASAN INTERNAL DALAM MEWUJUDKAN PEMERINTAH DAERAH YANG BAIK - H Achmad Fauzi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
Implementation of local government as regulated by Law Number 23 Year 2014 contains three functions. The first function is the planning of activities of local government tasks that are acceded by the Regional Development Planning Agency (Bappeda), the second function is the implementation of the tasks of local government that are represented and implemented by the Regional Device Organization (OPD) in the local government, and the third function is supervision the implementation or implementation of local government implemented by the Regional Inspectorate as the supervisor of the local government. Internal supervision (Inspectorate) is formed in order for the implementation of loca government tasks that are run by all existing regional devices can run well, effective, efficient and effective on target according to predetermined plans. herefore, the Inspectorate's role in overseeing the tasks of all the Regional ApparatusOrganizations in the local government is very important. In order to obtain an effective supervision, it is necessary to meet two principles of supervision, namely first, is the existence of a specific plan and the giving of instructions; second, giving clear authority to subordinates. The first basic principle is a must, because the plan is a standard, a measure of the work performed by subordinates. If this principle is well executed, then the implementation of good local government will be achieved well too.